DESAIN SISTEM INFORMASI ADMINISTRASI DAN KEUANGAN PAUD UNTUK MENCAPAI AKREDITASI - andarwati, mardiana (MATICS, 2014)
In the preparatory process leading to accredited two-ECD is trying to meet the necessary requirements. Minimum requirements have been met and there are other constraints that compliance management standard components and Standard ï¬nancing. Both of these will be easily met if there is a tool that is able to integrate all the activities that can generate reports quickly, complete and accurate. Data and information is complete and accurate order management requirements can be open, transparent and accountable. In both early childhood education, and ï¬nancial data management systems are still done manually. On the other hand increasing the number of students themselves. It often makes power and the system is usually enough to be able to handle it anymore. Information is oï¬en slow to parents, teachers who are also oï¬‚en diï¬‚icult to divide the administration section of time because of their time dealing with students becoming more complex. In addition, if there are certain policies relating to ï¬nances often take a long time because the data are correctly not all, data is still missing, incorrect calculations and so on. Therefore this activity is to help make the soï¬‚ware in data management and ï¬nancial administration of the manual into administrative and ï¬nancial information systems are computerized and integrated a collaboration of Microsoft Access and Visual Basic with Windows platform. Training and assistance in this activity is also carried out to ensure the success of the use of this software. Keywords : Paud, accreditation, information system